Rectovaginal Fistula Due To Chronic Perineal Tear; A Case Report - Yulia Margaretta Sari; Juan Habli Soufal (Yayasan Literasi Sains Indonesia, 2024)
An abnormal connection that exists between two epithelial surfaces or lumens of the rectum that reaches into the vagina is known as a recto-vaginal fistula (RVF). RVF is one unfortunate consequence of the underlying condition, such as trauma or surgery. According to the patient recap of the urogynecology clinic at M Djamil Hospital Padang (2023), from January to September, 6 patients had cases of rectovaginal fistula that needed to be repaired. Treatment of the underlying condition, the fistula, and its associated complications all fall under the umbrella of RVF management. Given that obstetrics, procedure is still the main cause in this case, the role of the field of urogynecology in the management of surgical interventions is important to maintain the quality of life of a woman. In this case report we present a case report of a 24-year-old woman with rectovaginal fistula and anal incontinence caused by chronic total perineal tear. The patient complained of feces discharge from the vagina since giving spontaneous birth to the first. Physical examination found defects in the internal sphincter (IAS) and external sphincter (EAS) at 11 until 14 o'clock. The patient then underwent sphincteroplasty and perineorrhaphy and showed improvement after surgical intervention